(untitled) (E Conference Zone, 2022)
The article describes modern virtual technologies, the meaning and content of virtual reality, the directions of virtual research etiah, the causes and factors of the impact of virtualization on humanity in the system of information society in the lives of young people. The development of the information society, the development of online intelligence, the development and impact of the Internet, as well as non-traditional types of lessons in modern education were introduced.